Cover Feature: Impact of Surface Defects on LaNiO3 Perovskite Electrocatalysts for the Oxygen Evolution Reaction (Chem. Eur. J. 58/2021). Issue 58 (6th October 2021) - Arandiyan, Hamidreza; Mofarah, Sajjad S.; Wang, Yuan; Cazorla, Claudio; Jampaiah, Deshetti; Garbrecht, Magnus; Wilson, Karen; Lee, Adam F.; Zhao, Chuan; Maschmeyer, Thomas
Abstract : The impact of defect generation by thermal reduction on the structure and electrocatalytic performance of LaNiO3 has been examined in a combined experimental and theoretical approach. Surface defects, predominantly surface oxygen vacancies, promote oxygen evolution over LaNiO3 resulting in a significantly lower overpotential (380 mV) for a current density of 10 mA cm −2, faster kinetics (70.8 mV dec −1 Tafel slope) and superior stability in alkaline electrolytes to conventionally prepared LaNiO3 . More information can be found in the Full Paper by H. Arandiyan, Y. Wang, T. Maschmeyer et al. (DOI: 10.1002/chem.202102672 ).